2013
DOI: 10.5851/kosfa.2013.33.5.672
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rapid Sample Preparation Method and Monitoring for Cholesterol Content in Chicken Egg and Egg powder

Abstract: The aim of this study was to develop sample preparation method and evaluate the exact cholesterol content in egg and egg powder purchased from Korean markets, and to determine whether significant differences exist among various egg products, since a variety of products are available in Korean markets and there are no recent databases for cholesterol. To evaluate the cholesterol content in chicken egg sold in Korean local market, a simple method using non-heated saponification to determine cholesterol for emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
1
11
0
3
Order By: Relevance
“…However, it was greater than the cholesterol concentration in whole chicken eggs, i.e. 3046.00-3062.00, 2368.73, 562.68 µg/g, as described by numerous preceding works (Lioe et al, 2013;Naviglio et al, 2012;Park et al, 2013). Cholesterol content of chicken eggs in this study was 3720 µg/g, which was closed to that reported by USDA (2016) and Exler et al (2013).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, it was greater than the cholesterol concentration in whole chicken eggs, i.e. 3046.00-3062.00, 2368.73, 562.68 µg/g, as described by numerous preceding works (Lioe et al, 2013;Naviglio et al, 2012;Park et al, 2013). Cholesterol content of chicken eggs in this study was 3720 µg/g, which was closed to that reported by USDA (2016) and Exler et al (2013).…”
Section: Discussionsupporting
confidence: 52%
“…Saponification constitutes initial and crucial step to release cholesterol from the other components since saponification was reported capable of improving cholesterol concentration in egg yolk compared to sample without saponification (John et al, 2015). The use of KOH in saponification enables to hydrolyze disrupting components such as fatty acids and acyl glycerides (Ahn et al, 2012;Park et al, 2013), while its effect may depend on the concentration and heating time (Salimon et al, 2012;Souza et al, 2017). The modification in this procedure was made at the following conditions, including less amount of sample (1 g, from 6 g of standard method), KOH concentration, saponification time, and changing toluene with hexane for extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(df = 0.2 μm) SP-2560 capillary GC column (Supelco 24056, USA) and a flame ionization detector (FID) was used to separate and detect the fatty acid (Grob et al ., 2003; Park et al ., 2013). A running time of 67 min was employed for each sample solution.…”
Section: Methodsmentioning
confidence: 99%
“…FAs were extracted with hexane after adding 1 g of anhydrous sodium sulfate (MFDS, 2013) . For TGs, 5 mL of hexane was added to 0.1 g of the extracted fat and the samples were subjected to GC analysis (Park et al ., 2013) .…”
Section: Methodsmentioning
confidence: 99%